A high trans-zeatin nucleoside concentration in corms may promote the multileaf growth of Amorphophallus muelleri - Xue, Zhiqin; Huang, Feiyan; Liu, Jiani; Ke, Yanguo; Wei, Huanyu; Gao, Penghua; Qi, Ying; Yu, Lei (Frontiers in Plant Science, 2022)
Amorphophallus muelleri has a multileaf growth pattern different from that of other konjacs; however, the hormonal mechanism underlying this phenomenon is not clear. In this study, the levels of hormones closely related to the sprouting of the axillary bud, including five types of cytokinins, indole-3-acetic acid (IAA) and abscisic acid (ABA) were measured. In the second leaf sprouting stage, the content of trans-zeatin riboside (tZR) in corms increased more than 5000-fold over that in the dormancy period. Surprisingly, although the expression of CYP735A1 and CYP735A2, which synthesize the precursors for tZR was elevated at the second leaf sprouting stage, the expression of IPTs, which have key roles in cytokinin biosynthesis, did not change significantly. In addition, most cytokinin contents in leaves during the same period were significantly lower than those in corms. We speculate that the high cytokinin contents in the corms may not biosynthesized de novo in corms. In addition, the IAA content in the corms also considerably increased during the second leaf sprouting stage. Indole-3-acetaldehyde oxidase (AO1) and auxin efflux carrier PIN1A, presented relatively high expression levels in the same period. In contrast, ABA content, and the expression of NCED1, a rate-limiting enzyme in ABA biosynthesis, were suppressed at the second leaf sprouting stage. It is worth mentioning that N6-(Δ2-isopentenyl) adenosine (iP)-type cytokinins have a high content in corms in the dormant period that significantly decreases after the first leaf sprouting stage, which is completely different from the trend of tZR. By treating dormant corms with iP, the percentage of multibud plants increased, and the growth performance in terms of bud and root length was significantly higher than those of the control. This implies that iP-type cytokinins tend to play a role in promoting first seedling sprouting. Furthermore, there was a remarkable increase of the IAA content in both corms and roots under iP treatment but an inhibitory effect in buds. We speculate that the increase in the IAA content induced by iP is tissue specific. These results will assist in the understanding of the role of hormones, especially cytokinins, in the multileaf growth type of konjac.